Perceived Ease and Use of Electronic Information Resources (Eir) By Undergraduate Students of Private Universities in Oyo State Nigeria - Adetunla, Gbenga O. (African Journal of Education and Practice, 2016)
Purpose: University libraries are investing huge amount of money to provide useful and accessible information services to users in electronic format to enhance learning and research activities. In order to justify the investment made on electronic information resources, this study examined awareness, perceived ease and use of EIR by undergraduate students of private university in Oyo state, Nigeria. Methodology: The study adopted a descriptive survey design with a study population of 2,171 undergraduate students. Multi-stage sampling technique was used for selecting the sampled respondents for the study. Questionnaire was used for data collection which was analyzed using descriptive statistics and Pearson product moment correlation. Findings: The findings revealed that EIR was perceived to be complex, non-flexible and not easy to use. More so, the use of EIR does not meet the information needs of the students. The major challenge faced by student when using EIR was found to be frequent power cut with 75% respondent rate. The finding also revealed a positive relationship between perceived ease and use of EIR at (p=0.00; p<0.05). Study Conclusions and policy recommendations: The study concluded that the students perceived EIR as complex and not flexible to use. Therefore, the study recommended that libraries should do more by providing technical support and training to ensure optimal use of EI.